Effect of bleaching with hydrogen peroxide into different concentrations on shear strength of brackets bonded with a resin-modified glass ionomer - Matheus Melo Pithon; Antônio Carlos de Oliveira Ruellas; Eduardo Franzotti Sant'anna (Universidade Estadual de Campinas, 2016)
The evolution in glass ionomer cements has contributed to the reduction in dental caries in orthodontic patients because of the biological and chemical characteristics of this material; however no studies in the literature have evaluated the effect of bleaching treatment on the bond strength values of resin-modified glass ionomer cements (RMGICs). This study assessed the effect of a 6, 7.5 and 35% hydrogen peroxide bleaching gel on shear bond strength and bond failure site of brackets bonded with a resin-modified glass ionomer (Fuji Ortho LC, GC Europe, Leuven, Belgium). One hundred-fifty bovine mandibular permanent incisors were randomly divided into 10 groups; each group contained 15 teeth. Bleaching treatment was performed immediately at 2 different times before the bonding procedure. One hundred-fifty stainless steel brackets were bonded with the resin-modified glass ionomer. Following, all samples were stored in distilled water for 24 hours and then tested in shear mode on a Instron machine. ANOVA and Tukey's test showed statistical differences between the groups whose teeth were treated with 7.5% hydrogen peroxide and the control group. However, no statistical differences were found for the other groups (P > 0.05). With respect to adhesive remnant index (ARI), the majority of fractures occurred at the bracket/composite interface. Despite the decreased shear bond strength, the bonding of teeth whitened with different concentrations of hydrogen peroxide was found to be strong enough to resist mechanical and masticatory forces.